Pengembangan Prototipe dan Uji Kinerja Perontok Pokem (Setaria italica L.) Mekanis Sistem Lepas - Paulus Payung; Abadi Jading; Reniana Reniana (The University of Lampung, 2021)
Pokem or Wheat Papua is one of the local food sources for the Papuan people which has a very strategic cultural value, especially at Numfor Island as a center for pokem production in Papua. Postharvest handling of pokem, specifically, threshing is still done conventionally with very limited threshing capacity. To optimize postharvest handling of pokem, specifically in the threshing process, a threshing machine is needed that can work more quickly and efficiently. The purpose of this study was to develop a prototype mechanical pokem thresher with a throw-in system with a combustion motor in order to further increase the efficiency and capacity of threshing. This research was conducted by designing a prototype mechanical pokem thresher and then performing a performance evaluation. The result of this research is that a prototype mechanical pokem thresher with a throw-in system has been formed which has functioned as a mechanical pokem thresher. The average results of the pokem thresher evaluation obtained threshing capacity of 36.29 kg/hour, threshing efficiency of 92.5% and percentage losses of 7.33%. Keywords: Biak Numfor, evaluation, local food, pokem thresher, wheat Papua